2019
DOI: 10.1155/2019/5096860
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Circulating ANGPTL8/Betatrophin Concentrations and Adult Obesity: A Meta-Analysis

Abstract: In this study, we evaluated the relationship between circulating betatrophin levels and obesity. Obesity is a common public health problem that is increasing globally. Betatrophin, a newly identified protein, is predominantly expressed in white and brown fat tissues and in the liver. Growing evidence suggests that betatrophin plays a pivotal role in metabolism, including the synthesis and degradation of lipids in cells, and adipocyte differentiation. Previous studies have assessed the association between circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…49 In clinical studies, levels of ANGPTL8 in the circulation of obese and overweight patients increases significantly. 40 The T allele at rs2278426 of ANGPTL8 represents Arg59Trp replacement, but the circulating level of ANGPTL8 is not affected. 50 Bioinformatis analysis has shown that Arg59Trp replacement caused by the T allele can reduce stability of the ANGPTL8 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In clinical studies, levels of ANGPTL8 in the circulation of obese and overweight patients increases significantly. 40 The T allele at rs2278426 of ANGPTL8 represents Arg59Trp replacement, but the circulating level of ANGPTL8 is not affected. 50 Bioinformatis analysis has shown that Arg59Trp replacement caused by the T allele can reduce stability of the ANGPTL8 protein.…”
Section: Discussionmentioning
confidence: 99%
“…31,39 Clinical studies have shown that the level of circulating ANGPTL8 in obese and overweight patients is significantly increased. 40 Therefore, ANGPTL8 may be involved in the occurrence and development of T2DM and its macrovascular lesions through its important regulatory role in glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of betatrophin levels in various forms of human insulin resistance were quite conflictory, partly due to the differences in measurement methods[ 82 ]. Later studies using more standardized methods for measuring betatrophin were summarized by several meta-analyses on the correlation of circulating betatrophin levels and type 2 diabetes, gestational diabetes, polycystic ovary syndrome (PCOS), and obesity — all conditions with insulin resistance[ 91 - 95 ]. Xu et al [ 91 ] analyzed 25 such studies and showed a positive and significant correlation between circulating betatrophin levels and insulin resistance.…”
Section: Novel Endocrine Functions Of the Livermentioning
confidence: 99%
“…Varikasuvu et al [ 94 ] analyzed 11 studies on betatrophin in PCOS and concluded that betatrophin is significantly elevated in PCOS. Similarly, Ye et al [ 95 ] analyzed 6 studies on betatrophin in obesity and concluded that betatrophin is significantly elevated in obesity. Thus, overall, circulating betatrophin is likely a marker of insulin resistance in humans.…”
Section: Novel Endocrine Functions Of the Livermentioning
confidence: 99%
“…Some studies have shown that ANGPTLs play an important role in insulin resistance, glucose metabolism, and hormone regulation [ 10 12 ]. Notably, ANGPTL8, also known as betatrophin, C19ORF80, or lipasin [ 13 ], regulates triglyceride metabolism by interacting with ANGPTL3 and ANGPTL4 to inhibit lipoprotein lipase (LPL) activity [ 14 16 ]. This further indicates that ANGPTLs are also closely related to lipid metabolism and may be an important link in metabolic syndrome [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%